Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3109/14647270903377186
|View full text |Cite
|
Sign up to set email alerts
|

Deciding the fate of supernumerary frozen embryos: parents' choices

Abstract: Embryo cryopreservation is a routine procedure in assisted reproductive technologies. Although couples have been informed about all potential procedures, some of them face the dilemma of what to do with surplus frozen embryos. The purpose of this qualitative study was to evaluate the attitude of patients toward their surplus cryopreserved embryos. Fifty patients who had undergone successful IVF cycles, and had surplus embryos cryopreserved were selected from a clinical database. We could contact twenty two pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
0
25
0
3
Order By: Relevance
“…Much of the available research into embryo donation for reproductive use considers general IVF patient attitudes; exploring why patients do not donate (Kingsberg et al ., 2000; Newton et al ., 2003; Bangsboll et al ., 2004; de Lacey 2005; Lyerly et al ., 2006, 2010; Fuscaldo et al ., 2007; Newton et al ., 2007; McMahon and Saunders, 2009; Melamed et al ., 2009; Mohler-Kuo et al ., 2009; Nachtigall et al ., 2009; Takahashi et al ., 2012; Wanggren et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Much of the available research into embryo donation for reproductive use considers general IVF patient attitudes; exploring why patients do not donate (Kingsberg et al ., 2000; Newton et al ., 2003; Bangsboll et al ., 2004; de Lacey 2005; Lyerly et al ., 2006, 2010; Fuscaldo et al ., 2007; Newton et al ., 2007; McMahon and Saunders, 2009; Melamed et al ., 2009; Mohler-Kuo et al ., 2009; Nachtigall et al ., 2009; Takahashi et al ., 2012; Wanggren et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Those electing to discard their embryos often cite ambivalence toward the cryopreservation process or partner disagreement toward disposition; thus, discarding provides a de fi nitive outcome. Melamed et al reported that most couples who chose to discard embryos stated it was "a last minute decision"; in addition, the majority did not agree with embryo research and were unable to donate their embryos to another couple [ 40 ] . Hammerberg and Tinney showed that although most couples preferred to donate their embryos to science/research or other couples rather than to discard them, those that elected disposal cited "not wanting a full sibling to existing children" and "opposition to embryo research" for choosing to dispose of their embryos [ 41 ] .…”
Section: To Whom Do Recipients Donate Their Embryos?mentioning
confidence: 99%
“…In contrast, patients whose decision-making was in fl uenced by religion were much less likely to have their embryos discarded. Therefore, countries that are predominantly Catholic (e.g., Brazil, Italy) have a very low incidence of embryo discardation [ 40 ] .…”
Section: To Whom Do Recipients Donate Their Embryos?mentioning
confidence: 99%
“…Consecuentemente, un estudio del año 2009 demuestra que las parejas participantes fueron más propensas a donar sus embriones para investigación antes que descartarlos, lo que también puede relacionarse con la decisión de no "desperdiciar" los embriones sobrantes. 11 Además de la importancia que reviste el contexto legal y normativo a la hora de tomar las decisiones, aparecen otros factores vinculados a los aspectos emocionales y familiares, a las creencias, a la cantidad de tratamientos realizados, al tiempo de búsqueda de embarazo y fundamentalmente al nacimiento de los hijos. En este contexto nos preguntamos ¿cómo perciben los pacientes a sus embriones criopreservados?…”
Section: Introductionunclassified
“…Un cuarto de los encuestados (25%) contestó que aún no han tomado una decisión. Estudios anteriores han demostrado que la representación del embrión es un factor fundamental a la hora de decidir qué hacer con los embriones excedentes [4][5]9,11,[14][15][16][17][18][19][20] . Sin embargo, los modos de representar están cultural y simbólicamente determinados y pueden ser co-construidos en el devenir del proceso reproductivo.…”
unclassified